The culture of sweet sorghum: review (Research, Society and Development, 2021)
The sweet sorghum is a grass of great agricultural importance, presents an annual cycle, erect and succulent stems with high sugar contents, and can be cultivated in tropical and subtropical regions around the world. The crop presents itself as one of the renewable sources capable of contributing to the increase in ethanol production, and can be used as a complementary crop to sugar cane. In this context, the objective was to review the available literature on the potentialities of the cultivation of sweet sorghum. The study presented is of a qualitative nature and is a literature review with the objective of gathering information on the cultivation and use of sweet sorghum and synthesizing them in a document, mainly for didactic use. Based on the observations and research carried out, it was possible to verify that, although sweet sorghum has potential for ethanol production, the crop is still little used in the country. These researchers showed that the production of biofuels is in constant evolution, so the cultivation of sweet sorghum will assist in the development of this scenario. The evaluation of new possibilities with the use of sweet sorghum in ethanol production is strategically important for the country, because it promotes the advance in the generation of knowledge, improvement of product quality and incorporation of production processes with less environmental impact, allowing the strengthening of the ethanol production system, as well as its diversification.